Parâmetros da pulverização na faixa de distribuição com VANT utilizando diferentes tamanhos de gotas na aplicação de herbicida - Robes, Rogério (My University, 2026)
This study aimed to evaluate the spray swath width and deposition characteristics of an unmanned aerial vehicle (UAV) operating with different droplet sizes in the application of a contact herbicide. The tested volumetric median diameters (VMD) were 100, 200, 300, 400, and 500 µm. The experiment followed a randomized complete block design with 15 treatments and three replications. Water-sensitive papers were positioned at 1.0 m intervals along a 14 m transect and mounted on metal supports 0.5 m above ground level to quantify droplet deposition. Each treatment replication covered an area of 1,500 m² (50 m × 30 m). For spray quality assessment, each water-sensitive paper was considered an experimental unit, whereas for desiccation evaluation, replications corresponded to the measured desiccated swaths within each treatment strip. Applications were performed using a DJI™ Agras T40 UAV equipped with two LX8060SZ™ rotary atomizers, calibrated to deliver 10 L ha⁻¹ at a flight speed of 5.6 m s⁻¹ and an operational height of 4.0 m above the target. The experiment was conducted in three different areas in the municipality of Palmeira, Paraná, Brazil. Spray deposition parameters were analyzed using the DropScope™ system, including covered area percentage, recovered spray volume (L ha⁻¹), droplet density (impacts cm⁻²), drift risk potential (percentage of droplets smaller than 150 µm), droplet diameters corresponding to 10%, 50%, and 90% of cumulative volume (DV0.1, DV0.5, and DV0.9), relative span (SPAN), and droplet size coefficient of variation (%). In addition, the effective desiccation swath was measured 15 days after application. Results demonstrated that covered area, recovered volume, droplet density, and droplet size variability were higher in the central sampling positions, particularly when larger droplets were used. Drift risk potential was lower in the central portion of the swath and increased toward the outer limits. Larger droplet diameters were predominantly observed in the central zone. Based on deposition data, the effective spray swath was 14 m for droplet sizes between 100 and 200 µm and 12 m for droplets larger than 300 µm. SPAN values indicated a homogeneous droplet size distribution. Field desiccation measurements showed swath widths of 14.5 m for 100 µm droplets, 12.8 m for 200 µm, 11.7 m for 300 µm, 10.0 m for 400 µm, and 8.3 m for 500 µm.
Keywords: agricultura de precisão; amplitude relativa; drone; tecnologia de aplicação; precision agriculture; relative amplitude (SPAN); application technology; desiccation